Ultrahigh-temperature-resistant anti-oxidation ceramic coating and preparation method thereof

By using four-layer coating structure and pressurized curing technology on carbon/carbon or carbon ceramic composites, the problem of its inability to resist oxidation in ultra-high temperature environment of 2000℃ is solved, and a longer period of high temperature oxidation resistance and better erosion resistance and thermal shock resistance are achieved.

CN119841667AActive Publication Date: 2025-04-18YANTAI KAIBO COMPOSITE MATERIAL TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510063130.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-18
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

Existing carbon/carbon or carbon ceramic composites cannot achieve oxidation resistance under ultra-high temperature environment of 2000℃, which seriously limits its performance.

Method used

The four-layer coating structure is adopted, including a transition layer, a sealing layer, an oxygen barrier layer and an erosion-resistant layer. By selecting materials with similar thermal expansion coefficients, the stability and adhesion of the coating are ensured by selecting materials with similar thermal expansion coefficients.

Benefits of technology

Long-term antioxidation of carbon/carbon or carbon ceramic composite materials in the high temperature range of 1500-2000°C is achieved, and its erosion resistance and thermal shock resistance are enhanced under ultra-high temperature airflow erosion conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841667A_ABST
    Figure CN119841667A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite ceramic coatings, in particular to an ultrahigh-temperature-resistant anti-oxidation ceramic coating and a preparation method thereof. The preparation method comprises the following steps: preparing the transition layer: mixing amorphous silicon dioxide, crystalline silicon dioxide, an adhesive and a solvent in proportion to obtain transition layer slurry; adhering to a base material, and pressurizing and curing to obtain A; preparing a sealing layer: mixing a mixture of SiO2 and B2O3, phenolic resin and alcohol in proportion to obtain sealing layer slurry; adhering to A, and curing to obtain B; preparing an oxygen barrier layer: mixing Si3N4 or SiC or a mixture of the Si3N4 and the SiC, phenolic resin and alcohol in proportion to obtain oxygen barrier layer slurry; adhering to B, and curing to obtain C; preparing an anti-erosion layer: uniformly mixing and stirring a mixture of ZrSiO4 and SiC, phenolic resin and alcohol in proportion to obtain anti-erosion layer slurry; adhering to the C, and curing to obtain D; and performing anaerobic high-temperature sintering. The invention relates to an anti-oxidation ceramic coating capable of resisting the high temperature of 2000 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite ceramic coatings, and more specifically, to an ultra-high temperature resistant and anti-oxidation ceramic coating and a preparation method thereof. Background Art

[0002] Carbon / carbon or carbon-ceramic composites are composite materials with carbon fiber reinforced carbon matrix. They have excellent properties such as high temperature resistance, low density, high specific modulus, high specific strength, thermal shock resistance, corrosion resistance, good friction performance, good vibration absorption, and small thermal expansion coefficient, which are unmatched by other structural materials. Especially in high temperature environments above 1500°C, the strength of carbon / carbon or carbon-ceramic composites does not decrease, but tends to increase, making them widely used in aviation, aerospace, metallurgy, medical and other fields. However, carbon / carbon or carbon-ceramic composites are easily oxidized at high temperatures, which seriously limits their performance. With the continuous development of aerospace technology, high-performance aircraft are developing towards high speed, high pressure resistance, and high temperature resistance, which puts higher requirements on the oxidation resistance, erosion resistance, and ablation resistance of carbon / carbon or carbon-ceramic composites.

[0003] At present, the methods for anti-oxidation of carbon / carbon or carbon-ceramic composite materials are mainly divided into two categories: one is the internal matrix modification technology based on the premise of the material itself to catalyze the oxidation reaction, and the other is the external anti-oxidation coating technology based on the premise of preventing oxygen contact and diffusion. Compared with the matrix modification technology, the anti-oxidation coating technology can achieve oxidation protection for a longer time and higher temperature range. It is the most direct and effective method to improve the anti-oxidation performance of composite materials, and it is also one of the most promising and widely studied methods.

[0004] However, the current anti-oxidation temperature of carbon / carbon or carbon-ceramic composite materials is below 1500°C, and they cannot achieve the anti-oxidation purpose in an ultra-high temperature environment of 2000°C. Summary of the invention

[0005] In order to improve the temperature resistance of the anti-oxidation coating, the present application provides an ultra-high temperature resistant anti-oxidation ceramic coating and a preparation method thereof.

[0006] In a first aspect, the present application provides a method for preparing an ultra-high temperature resistant and anti-oxidation ceramic coating, which adopts the following technical solution: A method for preparing an ultrahigh temperature resistant and anti-oxidation ceramic coating comprises the following steps: (1) Preparation of transition layer Preparing a transition layer slurry: mixing amorphous silicon dioxide, crystalline silicon dioxide, an adhesive, and a solvent in a ratio of (2-4):(1-2):(1-2):(0.5-1), stirring and dispersing the mixture evenly to obtain a transition layer slurry; The transition layer slurry is adhered to the substrate, placed in a curing furnace, and pressurized to obtain A; (2) Preparation of sealing layer Preparation of sealing layer slurry: Mix a mixture of SiO2 and B2O3 in a ratio of (1-2):(2-3), phenolic resin, and alcohol in a ratio of (1-2):(0.5-1):(0.5-1) and stir well to obtain sealing layer slurry; The sealing layer slurry is adhered to A and solidified to obtain B; (3) Preparation of oxygen barrier layer Preparing oxygen barrier layer slurry: mixing Si3N4 or SiC or a mixture of Si3N4 and SiC, phenolic resin, and alcohol in a ratio of (1-2):(0.5-1):(0.5-1) and stirring to obtain oxygen barrier layer slurry; The oxygen barrier layer slurry is adhered to B and cured to obtain C; (4) Preparation of anti-erosion layer Preparation of anti-erosion layer slurry: Mix ZrSiO4 and SiC in a ratio of (0.5-1): (1-2), phenolic resin, and alcohol in a ratio of (1-2): (0.5-1): (0.5-1) and stir evenly to obtain anti-erosion layer slurry; The anti-erosion layer slurry is adhered to C and solidified to obtain D; (5) Sinter D at high temperature in an oxygen-free environment.

[0007] By adopting the above technical solution, the transition layer is composed of SiO2; the sealing layer is composed of SiO2-B2O3; the oxygen barrier layer is composed of Si3N4 or SiC; and the anti-erosion layer is composed of ZrSiO4-SiC. The anti-oxidation coating is prepared layer by layer using materials with similar thermal expansion coefficients, which can avoid cracks and coating shedding caused by large differences in thermal expansion coefficients between coatings, thereby ensuring the durability of the high-temperature resistant anti-oxidation coating.

[0008] The two elements of silicon nitride have similar electronegativity and are strong covalently bonded compounds. The molecular structure of silicon nitride is complex and diverse. Each silicon atom forms an equivalent Si-N chemical bond with eight nitrogen atoms to form an octahedral structure, which is an atomic crystal and resistant to oxidation at high temperatures. It can also resist thermal shock and will not break even if it is heated to more than 1500°C in the air, cooled rapidly, and then heated rapidly.

[0009] The molecular structure of silicon carbide is formed by carbon and silicon atoms through covalent bonds and ionic bonds, and has two common crystal structures: cubic β-SiC and hexagonal α-SiC. This structure enables silicon carbide to maintain good physical and chemical properties at high temperatures, and has high hardness and wear resistance.

[0010] The structure of zirconium silicate is a complex silicate structure formed by silicon-oxygen tetrahedrons and zirconium ions through a specific connection method, which makes it have excellent anti-oxidation properties. The coating prepared by mixing ZrSiO4 and silicon carbide in a specific ratio has a very low oxygen permeability and can exist stably at high temperatures above 1500℃ without phase change and reaction, thus having good resistance to oxygen erosion corrosion.

[0011] Preferably, the adhesive is an inorganic adhesive, the inorganic adhesive is silica sol, the solvent is water, and a dispersant is added and stirred evenly to obtain the transition layer slurry.

[0012] Preferably, the adhesive is an organic adhesive, the organic adhesive is a phenolic resin, and the solvent is alcohol.

[0013] By adopting the above technical solution, the adhesive can be an organic adhesive or an inorganic adhesive, corresponding to different solvents, to achieve uniform dispersion and then adhesion.

[0014] Preferably, the transition layer slurry is adhered to the substrate by dipping, painting or electrophoresis, and the sealing layer, oxygen barrier layer and anti-erosion layer slurry are adhered by dipping or painting.

[0015] By adopting the above technical solution, the electrophoresis adhesion method is more uniform, but it can only be used when the substrate adheres to the first layer of coating, that is, the transition layer, because when other coatings are applied, the previous coatings attached to the substrate have been dried. If electrophoresis is used, the entire substrate needs to be immersed in liquid, which will make the dried coating unstable. Therefore, in comparison, dipping and brushing can meet the adhesion requirements of each coating.

[0016] Preferably, the curing method is: heating from room temperature to the first temperature, keeping warm for 30 minutes; heating to the second temperature, keeping warm for 30 minutes; heating to the third temperature, keeping warm for 20 minutes; heating to the fourth temperature, keeping warm for 20 minutes; heating to the fifth temperature, keeping warm for 30 minutes to perform the curing process; Wherein: first temperature: 80°C; second temperature: 100°C; third temperature: 120°C; fourth temperature: 150°C; fifth temperature: 200°C; The pressurized curing method is: pressurizing 1.5-1.8Mp at room temperature, and the fifth temperature is 180°C.

[0017] By adopting the above technical solution, the coating can be dried, so that the coating is stable and does not fall off, and stable transfer between various devices can be achieved. The transition layer adopts a unique pressurization curing process. Pressurization can press the material in the transition layer into the pores of the carbon-carbon composite material, reduce the mismatch of the thermal expansion coefficient between the transition layer and the substrate and between the transition layer and the sealing layer, and enhance the bonding force between the coating and the substrate.

[0018] It is cured at high temperature under pressure in a curing furnace. During the high temperature curing process, part of SiO2 is pressurized to penetrate into the pores of the carbon-carbon material. Finally, when sintered at 2000℃-2400℃ in a high temperature furnace, SiO2 forms a dense glass structure under high temperature conditions. The crystal phase is tetragonal, which can effectively prevent the chemical reaction between the sealing layer and the base material.

[0019] Preferably, the substrate is pretreated before preparing the coating, and the substrate is a carbon / carbon composite material. The carbon / carbon composite material is polished with SiC sandpaper, ultrasonically cleaned, and dried in an oven.

[0020] By adopting the above technical solution, the pretreatment can increase the roughness of the surface of the carbon-carbon composite material and enhance the bonding strength between the carbon-carbon composite material matrix and the transition layer.

[0021] The amorphous silicon dioxide is 300-400 mesh, and the crystalline silicon dioxide is -200 mesh.

[0022] By adopting the above technical solution, the crystalline silicon dioxide is glassy, ​​pore-free and more dense. The adjacent atoms of each amorphous silicon dioxide are arranged regularly, but the whole structure is deformed, so the structure is not as dense as the crystalline silicon dioxide. Only when the two are mixed with such mesh size and proportion can the transition layer and the substrate be more closely and fully connected.

[0023] Preferably, the high temperature sintering temperature in the oxygen-free environment is 2000°C-2400°C.

[0024] By adopting the above technical solution, high-temperature sintering can solidify the four-layer coating and solidify it together with the substrate without cracking or falling off.

[0025] In a second aspect, the present application provides an ultra-high temperature resistant and anti-oxidation ceramic coating, which adopts the following technical solution: An ultra-high temperature resistant and anti-oxidation ceramic coating comprises a transition layer, a sealing layer, an oxygen barrier layer and an anti-erosion layer, wherein the transition layer comprises silicon dioxide, the sealing layer comprises SiO2 and B2O3, the oxygen barrier layer comprises Si3N4 or SiC or a mixture of Si3N4 and SiC, and the anti-erosion layer comprises ZrSiO4 and SiC.

[0026] By adopting the above technical solution, by setting four layers of coating, each layer is made of a material with a specific thermal expansion coefficient, and an anti-oxidation ceramic coating that can withstand a high temperature of 2000°C is obtained.

[0027] Preferably, the thickness of the transition layer coating is 0.2-0.3 mm, the thickness of the sealing layer coating is 0.1-0.2 mm, the thickness of the oxygen barrier layer coating is 0.2-0.3 mm, and the thickness of the anti-erosion layer coating is 0.3-0.4 mm.

[0028] By adopting the above technical solution, the outermost anti-erosion layer in contact with oxygen is the thickest, and the other layers are thinner. This thickness combination makes it easier to achieve oxygen blocking without cracking or falling off.

[0029] In summary, this application has the following beneficial effects: 1. The transition layer is composed of SiO2; the sealing layer is composed of SiO2-B2O3; the oxygen barrier layer is composed of Si3N4 or SiC; the anti-erosion layer is composed of ZrSiO4-SiC. Selecting materials with similar thermal expansion coefficients to prepare the anti-oxidation coating layer by layer can avoid cracks and coating shedding caused by large differences in thermal expansion coefficients between coatings, thereby ensuring the durability of the high-temperature resistant anti-oxidation coating.

[0030] Due to the different oxidation mechanisms of carbon / carbon or carbon-ceramic composites in different temperature ranges and the different anti-oxidation behaviors of different coating materials, it is difficult to use the same coating material to effectively protect different oxidation processes in the entire temperature range. Through the four-layer coating structure of transition layer, sealing layer, oxygen barrier layer and anti-erosion layer, while each coating material plays its own advantages, it also improves and avoids their respective shortcomings through mutual coordination and mutual complementation, thereby solving the current high-temperature oxidation problem of carbon / carbon or carbon-ceramic composites at 1500-2000℃.

[0031] 2. A unique pressurized curing process is used for the transition layer to reduce the mismatch in thermal expansion coefficients between the transition layer and the substrate, and between the transition layer and the sealing layer, and to enhance the bonding force between the coating and the substrate.

[0032] 3. The multi-layer composite coating of the prepared ultra-high temperature anti-oxidation ceramic coating can achieve oxidation protection for carbon / carbon or carbon-ceramic materials for a longer time and at a higher temperature range, and at the same time can show good erosion resistance and thermal shock stability under ultra-high temperature airflow erosion conditions.

[0033] 4. The present application solves the problem of rapid oxidation erosion of carbon / carbon or carbon-ceramic composite materials at ultra-high temperatures of 1500-2000°C through a uniquely designed four-layer coating structure, ensuring that the performance of carbon / carbon or carbon-ceramic composite materials is stable for a long time at a temperature of 1500-2000°C and in an oxygen environment, so that they can be better used in the aerospace field.

[0034] 5. Through the four-layer composite structure of anti-oxidation ceramic coating, the carbon / carbon or carbon-ceramic composite material can be resistant to oxidation for a long time in the ultra-high temperature range of 1500-2000℃, and at the same time can show good erosion resistance and thermal shock resistance stability under ultra-high temperature airflow erosion conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 : A simplified structural diagram of the anti-oxidation ceramic coating of this application. DETAILED DESCRIPTION

[0036] The following is combined with the embodiment and Figure 1 This application is described in further detail.

[0037] Carbon / carbon or carbon-ceramic composite anti-oxidation coatings can generally only withstand temperatures of 1500°C. Some of these anti-oxidation coatings are thinner and have poor oxygen barrier effects; others are thicker and have improved oxygen barrier effects, but have poor adhesion and thermal shock stability, and are prone to cracking or even falling off. Example

[0038] Example 1 1. Preparation of carbon / carbon composite material samples: The matrix, i.e. the carbon / carbon composite material, was polished with SiC sandpaper, ultrasonically cleaned for 30 minutes, and then dried in an oven at 180°C for 1 hour.

[0039] 2. Add transition layer Amorphous silicon dioxide (300 mesh): crystalline silicon dioxide (-200 mesh): silica sol: water = 2:1:1:0.5 were mixed, and sodium alginate was added as a dispersant after stirring for 30 minutes, and the stirring was continued for 30 minutes to obtain a transition layer slurry.

[0040] The prepared transition layer slurry is adhered to the substrate of the carbon / carbon composite material by electrophoresis, so that the thickness of the transition layer is 0.2mm. Transfer to the curing furnace for pressurized curing. Complete the pressurization to 1.8MPa at room temperature within 15 minutes. After the pressurization is completed, maintain the pressure of 1.8MPa, and perform the curing treatment according to the temperature increase curve from room temperature to the first temperature, keep warm for 30 minutes; heat up to the second temperature, keep warm for 30 minutes; heat up to the third temperature, keep warm for 20 minutes; heat up to the fourth temperature, keep warm for 20 minutes; heat up to the fifth temperature, keep warm for 30 minutes.

[0041] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 180°C.

[0042] The entirety of the substrate with the transition layer attached obtained after pressurization and curing is A.

[0043] 3. Add sealing layer After SiO2 and B2O3 are uniformly mixed in a ratio of 2:3: phenolic resin: alcohol = 1:0.5:0.5, stir for 1 hour to obtain a sealing layer slurry.

[0044] The obtained sealing layer slurry is adhered to the transition layer cured on the carbon-carbon composite material by the impregnation method, that is, adhered to one side of the transition layer on A, so that the thickness of the sealing layer is 0.1 mm, and the carbon-carbon composite material with the transition layer and the sealing layer adhered is transferred to an oven. The curing treatment is carried out according to the temperature increase curve from room temperature to the first temperature, and the temperature is kept for 30 minutes; the temperature is increased to the second temperature, and the temperature is kept for 30 minutes; the temperature is increased to the third temperature, and the temperature is kept for 20 minutes; the temperature is increased to the fourth temperature, and the temperature is kept for 20 minutes; the temperature is increased to the fifth temperature, and the temperature is kept for 30 minutes.

[0045] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 200°C.

[0046] The obtained substrate with the transition layer and the sealing layer attached is B.

[0047] On the one hand, the SiO2 contained in the sealing layer can better compound with the transition layer to prevent the coating from cracking and falling off due to the large difference in thermal expansion coefficients of the two materials; on the other hand, it can increase the sealing temperature, and the added alkaline earth oxide B2O3 can improve the sealing effect.

[0048] 4. Add oxygen barrier Si3N4:phenolic resin:alcohol=1:1:1 ratio was mixed and stirred for 1 hour to obtain the slurry of sealing layer coating.

[0049] The prepared oxygen barrier layer slurry was adhered to the carbon / carbon composite material after the sealing layer was cured by brushing, that is, adhered to one side of the sealing layer on B, so that the thickness of the oxygen barrier layer was 0.2 mm, and then transferred to an oven. The curing treatment was carried out according to the temperature increase curve from room temperature to the first temperature, and kept warm for 30 minutes; to the second temperature, and kept warm for 30 minutes; to the third temperature, and kept warm for 20 minutes; to the fourth temperature, and kept warm for 20 minutes; to the fifth temperature, and kept warm for 30 minutes.

[0050] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 200°C.

[0051] The resulting substrate with the transition layer, sealing layer and oxygen barrier layer attached is C.

[0052] Si3N4 has unique high temperature oxidation resistance.

[0053] The two elements of silicon nitride have similar electronegativity and are strong covalently bonded compounds. The molecular structure of silicon nitride is complex and diverse. Each silicon atom forms an equivalent Si-N chemical bond with eight nitrogen atoms to form an octahedral structure, which is an atomic crystal and resistant to oxidation at high temperatures. It can also resist thermal shock and will not break even if it is heated to more than 1500°C in the air, cooled rapidly, and then heated rapidly.

[0054] 5. Add anti-erosion layer After uniformly mixing ZrSiO4:SiC=1:2:phenolic resin:alcohol=1:1:1, stir for 1 hour to obtain the anti-erosion layer slurry.

[0055] The prepared anti-erosion layer slurry is adhered to the carbon / carbon composite material of the cured oxygen barrier layer by brushing, that is, adhered to one side of the oxygen barrier layer on C, so that the thickness of the anti-erosion layer is 0.3 mm, and then transferred to an oven for curing according to a heating curve of heating from room temperature to a first temperature, keeping warm for 30 minutes; heating to a second temperature, keeping warm for 30 minutes; heating to a third temperature, keeping warm for 20 minutes; heating to a fourth temperature, keeping warm for 20 minutes; heating to a fifth temperature, keeping warm for 30 minutes.

[0056] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 200°C.

[0057] The obtained substrate with the transition layer, sealing layer, oxygen barrier layer and anti-erosion layer attached is D.

[0058] The structure of zirconium silicate is a complex silicate structure formed by silicon-oxygen tetrahedrons and zirconium ions through a specific connection method, which makes it have excellent anti-oxidation properties. The coating prepared by mixing ZrSiO4 and silicon carbide in a specific ratio has a very low oxygen permeability and can exist stably at high temperatures above 1500℃ without phase change and reaction, thus having good resistance to oxygen erosion corrosion.

[0059] 6. High temperature furnace sintering The substrate and the prepared anti-oxidation ceramic coating, namely D, finally need to be sintered in a high-temperature furnace at 2200°C, and argon gas is filled for protection throughout the process. During the high-temperature curing process of the transition layer, part of the SiO2 is infiltrated into the pores of the carbon-carbon material by pressurization. Finally, when sintered in a high-temperature furnace at 2200°C, SiO2 forms a dense glass structure under high temperature conditions, and the crystal phase is a tetragonal system, which can effectively prevent the chemical reaction between the sealing layer and the substrate material.

[0060] Example 2 1. Preparation of carbon / carbon composite material samples: The matrix, i.e. the carbon / carbon composite material, was polished with SiC sandpaper, ultrasonically cleaned for 30 minutes, and then dried in an oven at 180°C for 1 hour.

[0061] 2. Add transition layer Amorphous 400-mesh silica: crystalline -200-mesh silica: phenolic resin: alcohol were mixed in a ratio of 2:1:1:0.5 and stirred for 1 hour to obtain a slurry.

[0062] The prepared slurry is adhered to the carbon / carbon composite material by impregnation, so that the thickness of the transition layer is 0.25mm, and then transferred to the curing furnace. Within 10 minutes, the room temperature is pressurized to 1.5MPa. After the pressurization is completed, the pressure is maintained at 1.5MPa, and the curing treatment is carried out according to the temperature increase curve from room temperature to the first temperature, and the temperature is kept for 30 minutes; the temperature is increased to the second temperature, and the temperature is kept for 30 minutes; the temperature is increased to the third temperature, and the temperature is kept for 20 minutes; the temperature is increased to the fourth temperature, and the temperature is kept for 20 minutes; the temperature is increased to the fifth temperature, and the temperature is kept for 30 minutes.

[0063] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 180°C.

[0064] 3. Add sealing layer After SiO2 and B2O3 are uniformly mixed in a ratio of 2:3: phenolic resin: alcohol = 1:1:1, the mixture is stirred for 1 hour to obtain a sealing layer slurry.

[0065] The obtained sealing layer slurry was applied to the transition layer of the carbon / carbon composite material by brushing, so that the thickness of the sealing layer was 0.15 mm, and then transferred to an oven. The curing treatment was carried out according to the temperature increase curve from room temperature to the first temperature, and kept warm for 30 minutes; to the second temperature, and kept warm for 30 minutes; to the third temperature, and kept warm for 20 minutes; to the fourth temperature, and kept warm for 20 minutes; to the fifth temperature, and kept warm for 30 minutes.

[0066] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 200°C.

[0067] 4. Add oxygen barrier SiC: phenolic resin: alcohol were mixed in a ratio of 1:1:1 and stirred for 1 hour to obtain a sealing layer slurry.

[0068] The prepared oxygen barrier slurry was applied to the sealing layer on the carbon / carbon composite material by brushing, so that the thickness of the oxygen barrier layer was 0.25 mm, and then transferred to an oven. The curing treatment was carried out according to the temperature increase curve from room temperature to the first temperature, and kept warm for 30 minutes; to the second temperature, and kept warm for 30 minutes; to the third temperature, and kept warm for 20 minutes; to the fourth temperature, and kept warm for 20 minutes; to the fifth temperature, and kept warm for 30 minutes.

[0069] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 200°C.

[0070] 5. Add anti-erosion layer After uniformly mixing ZrSiO4:SiC=1:1:phenolic resin:alcohol=1:1:1, stirring for 1 hour, obtain the slurry of anti-erosion layer coating.

[0071] The prepared coating slurry of the erosion-resistant layer is adhered to the oxygen barrier layer of the carbon / carbon composite material by brushing, so that the thickness of the erosion-resistant layer is 0.35 mm, and then transferred to an oven for curing according to a heating curve of heating from room temperature to a first temperature, keeping warm for 30 minutes; heating to a second temperature, keeping warm for 30 minutes; heating to a third temperature, keeping warm for 20 minutes; heating to a fourth temperature, keeping warm for 20 minutes; heating to a fifth temperature, keeping warm for 30 minutes.

[0072] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 200°C.

[0073] 6. High temperature furnace sintering The prepared anti-oxidation ceramic coating finally needs to be sintered in a high-temperature furnace at 2000°C, with nitrogen protection throughout the process.

[0074] Example 3 1. Preparation of carbon / carbon composite material samples: The matrix, i.e. the carbon / carbon composite material, was polished with SiC sandpaper, ultrasonically cleaned for 30 minutes, and then dried in an oven at 180°C for 1 hour.

[0075] 2. Add transition layer Amorphous silicon dioxide (300 mesh): crystalline silicon dioxide (-200 mesh): silica sol: water = 4:1:2:0.5 were mixed, and sodium alginate was added as a dispersant after stirring for 30 minutes, and the stirring was continued for 30 minutes to obtain a transition layer slurry.

[0076] The prepared transition layer slurry is adhered to the carbon / carbon composite material by brushing, so that the thickness of the transition layer is 0.3mm, and then transferred to the curing furnace for pressurized curing. The room temperature pressurization to 1.8MPa is completed within 15 minutes. After the pressurization is completed, the pressure is maintained at 1.8MPa, and the curing treatment is carried out according to the temperature increase curve from room temperature to the first temperature, and the temperature is kept for 30 minutes; the temperature is increased to the second temperature, and the temperature is kept for 30 minutes; the temperature is increased to the third temperature, and the temperature is kept for 20 minutes; the temperature is increased to the fourth temperature, and the temperature is kept for 20 minutes; the temperature is increased to the fifth temperature, and the temperature is kept for 30 minutes.

[0077] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 180°C.

[0078] 3. Add sealing layer After SiO2 and B2O3 are uniformly mixed in a ratio of 1:3: phenolic resin: alcohol = 2:0.5:1, the mixture is stirred for 1 hour to obtain a sealing layer slurry.

[0079] The obtained sealing layer slurry is adhered to the transition layer cured on the carbon-carbon composite material by an impregnation method, so that the thickness of the sealing layer is 0.2 mm, and the carbon-carbon composite material with the transition layer and the sealing layer adhered is transferred to an oven. The curing treatment is carried out according to the temperature increase curve from room temperature to the first temperature, and the temperature is kept for 30 minutes; the temperature is increased to the second temperature, and the temperature is kept for 30 minutes; the temperature is increased to the third temperature, and the temperature is kept for 20 minutes; the temperature is increased to the fourth temperature, and the temperature is kept for 20 minutes; the temperature is increased to the fifth temperature, and the temperature is kept for 30 minutes.

[0080] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 200°C.

[0081] On the one hand, the SiO2 contained in the sealing layer can better compound with the transition layer to prevent the coating from cracking and falling off due to the large difference in thermal expansion coefficients of the two materials; on the other hand, it can increase the sealing temperature, and the added alkaline earth oxide B2O3 can improve the sealing effect.

[0082] 4. Add oxygen barrier Si3N4:phenolic resin:alcohol=2:0.5:1 were mixed and stirred for 1 hour to obtain the slurry of sealing layer coating.

[0083] The prepared oxygen barrier layer slurry was applied to the carbon / carbon composite material after curing the sealing layer by brushing, so that the thickness of the oxygen barrier layer was 0.3 mm, and then transferred to an oven. The curing treatment was carried out according to the temperature increase curve from room temperature to the first temperature, and kept warm for 30 minutes; to the second temperature, and kept warm for 30 minutes; to the third temperature, and kept warm for 20 minutes; to the fourth temperature, and kept warm for 20 minutes; to the fifth temperature, and kept warm for 30 minutes.

[0084] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 200°C.

[0085] Si3N4 has unique high temperature oxidation resistance.

[0086] The two elements of silicon nitride have similar electronegativity and are strong covalently bonded compounds. The molecular structure of silicon nitride is complex and diverse. Each silicon atom forms an equivalent Si-N chemical bond with eight nitrogen atoms to form an octahedral structure, which is an atomic crystal and resistant to oxidation at high temperatures. It can also resist thermal shock and will not break even if it is heated to more than 1500°C in the air, cooled rapidly, and then heated rapidly.

[0087] 5. Add anti-erosion layer After uniformly mixing ZrSiO4:SiC=1:4:phenolic resin:alcohol=2:0.5:1, stir for 1 hour to obtain the anti-erosion layer slurry.

[0088] The prepared anti-erosion layer slurry is adhered to the carbon / carbon composite material of the cured oxygen barrier layer by brushing, so that the thickness of the anti-erosion layer is 0.4 mm, and then transferred to an oven for curing according to a heating curve of heating from room temperature to a first temperature, keeping warm for 30 minutes; heating to a second temperature, keeping warm for 30 minutes; heating to a third temperature, keeping warm for 20 minutes; heating to a fourth temperature, keeping warm for 20 minutes; heating to a fifth temperature, keeping warm for 30 minutes.

[0089] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 200°C.

[0090] The structure of zirconium silicate is a complex silicate structure formed by silicon-oxygen tetrahedrons and zirconium ions through a specific connection method, which makes it have excellent anti-oxidation properties. The coating prepared by mixing ZrSiO4 and silicon carbide in a specific ratio has a very low oxygen permeability and can exist stably at high temperatures above 1500℃ without phase change and reaction, thus having good resistance to oxygen erosion corrosion.

[0091] 6. High temperature furnace sintering The prepared anti-oxidation ceramic coating needs to be sintered at 2200℃ in a high-temperature furnace, and argon gas is filled for protection throughout the process. During the high-temperature curing process of the transition layer, some SiO2 is infiltrated into the pores of the carbon-carbon material by pressurization. Finally, when sintered at 2200℃ in a high-temperature furnace, SiO2 forms a dense glass structure under high temperature conditions, and the crystal phase is a tetragonal system, which can effectively prevent the chemical reaction between the sealing layer and the base material.

[0092] Example 4 1. Preparation of carbon / carbon composite material samples: The matrix, i.e. the carbon / carbon composite material, was polished with SiC sandpaper, ultrasonically cleaned for 30 minutes, and then dried in an oven at 180°C for 1 hour.

[0093] 2. Add transition layer Amorphous silicon dioxide (400 mesh): crystalline silicon dioxide (-200 mesh): phenolic resin: alcohol in a ratio of 2:2:1:1 were mixed and stirred for 1 hour to obtain a slurry.

[0094] The prepared transition layer slurry is adhered to the carbon / carbon composite material by electrophoresis, so that the thickness of the transition layer is 0.2mm, and then transferred to the curing furnace for pressurized curing. The room temperature pressurization to 1.6MPa is completed within 15 minutes. After the pressurization is completed, the pressure is maintained at 1.6MPa, and the curing treatment is carried out according to the temperature increase curve from room temperature to the first temperature, and the temperature is kept for 30 minutes; the temperature is increased to the second temperature, and the temperature is kept for 30 minutes; the temperature is increased to the third temperature, and the temperature is kept for 20 minutes; the temperature is increased to the fourth temperature, and the temperature is kept for 20 minutes; the temperature is increased to the fifth temperature, and the temperature is kept for 30 minutes.

[0095] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 180°C.

[0096] 3. Add sealing layer After SiO2 and B2O3 are uniformly mixed in a ratio of 1:1: phenolic resin: alcohol = 1:1:0.5, stir for 1 hour to obtain a sealing layer slurry.

[0097] The obtained sealing layer slurry is adhered to the transition layer cured on the carbon-carbon composite material by an impregnation method, so that the thickness of the sealing layer is 0.1 mm, and the carbon-carbon composite material with the transition layer and the sealing layer adhered is transferred to an oven. The curing treatment is carried out according to the temperature increase curve from room temperature to the first temperature, and the temperature is kept for 30 minutes; the temperature is increased to the second temperature, and the temperature is kept for 30 minutes; the temperature is increased to the third temperature, and the temperature is kept for 20 minutes; the temperature is increased to the fourth temperature, and the temperature is kept for 20 minutes; the temperature is increased to the fifth temperature, and the temperature is kept for 30 minutes.

[0098] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 200°C.

[0099] On the one hand, the SiO2 contained in the sealing layer can better compound with the transition layer to prevent the coating from cracking and falling off due to the large difference in thermal expansion coefficients of the two materials; on the other hand, it can increase the sealing temperature, and the added alkaline earth oxide B2O3 can improve the sealing effect.

[0100] 4. Add oxygen barrier SiC: phenolic resin: alcohol = 1:1:0.5 were mixed and stirred for 1 hour to obtain a slurry for the sealing layer coating.

[0101] The prepared oxygen barrier slurry was applied to the carbon / carbon composite material after curing the sealing layer by brushing, so that the thickness of the oxygen barrier layer was 0.2 mm, and then transferred to an oven. The curing treatment was carried out according to the temperature increase curve from room temperature to the first temperature, and kept warm for 30 minutes; to the second temperature, and kept warm for 30 minutes; to the third temperature, and kept warm for 20 minutes; to the fourth temperature, and kept warm for 20 minutes; to the fifth temperature, and kept warm for 30 minutes.

[0102] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 200°C.

[0103] SiC has unique high temperature oxidation resistance.

[0104] The molecular structure of silicon carbide is formed by carbon and silicon atoms through covalent bonds and ionic bonds, and has two common crystal structures: cubic β-SiC and hexagonal α-SiC. This structure enables silicon carbide to maintain good physical and chemical properties at high temperatures, and has high hardness and wear resistance.

[0105] 5. Add anti-erosion layer After uniformly mixing ZrSiO4:SiC in a ratio of 1:1:phenolic resin:alcohol in a ratio of 1:1:0.5, stir for 1 hour to obtain an anti-erosion layer slurry.

[0106] The prepared anti-erosion layer slurry is adhered to the carbon / carbon composite material of the cured oxygen barrier layer by brushing, so that the thickness of the anti-erosion layer is 0.3 mm, and then transferred to an oven for curing according to a heating curve of heating from room temperature to a first temperature, keeping warm for 30 minutes; heating to a second temperature, keeping warm for 30 minutes; heating to a third temperature, keeping warm for 20 minutes; heating to a fourth temperature, keeping warm for 20 minutes; heating to a fifth temperature, keeping warm for 30 minutes.

[0107] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 200°C.

[0108] The structure of zirconium silicate is a complex silicate structure formed by silicon-oxygen tetrahedrons and zirconium ions through a specific connection method, which makes it have excellent anti-oxidation properties. The coating prepared by mixing ZrSiO4 and silicon carbide in a specific ratio has a very low oxygen permeability and can exist stably at high temperatures above 1500℃ without phase change and reaction, thus having good resistance to oxygen erosion corrosion.

[0109] 6. High temperature furnace sintering The prepared anti-oxidation ceramic coating needs to be sintered at 2200℃ in a high-temperature furnace, and argon gas is filled for protection throughout the process. During the high-temperature curing process of the transition layer, some SiO2 is infiltrated into the pores of the carbon-carbon material by pressurization. Finally, when sintered at 2200℃ in a high-temperature furnace, SiO2 forms a dense glass structure under high temperature conditions, and the crystal phase is a tetragonal system, which can effectively prevent the chemical reaction between the sealing layer and the base material.

[0110] Example 5 1. Preparation of carbon / carbon composite material samples: The matrix, i.e. the carbon / carbon composite material, was polished with SiC sandpaper, ultrasonically cleaned for 30 minutes, and then dried in an oven at 180°C for 1 hour.

[0111] 2. Add transition layer Amorphous silicon dioxide (300 mesh): crystalline silicon dioxide (-200 mesh): phenolic resin: alcohol in a ratio of 2:2:1:1 were mixed and stirred for 1 hour to obtain a slurry.

[0112] The prepared transition layer slurry is adhered to the carbon / carbon composite material by electrophoresis, so that the thickness of the transition layer is 0.3mm, and then transferred to the curing furnace for pressurized curing. The room temperature pressurization to 1.8MPa is completed within 15 minutes. After the pressurization is completed, the pressure is maintained at 1.8MPa, and the curing treatment is carried out according to the temperature increase curve from room temperature to the first temperature, and the temperature is kept for 30 minutes; the temperature is increased to the second temperature, and the temperature is kept for 30 minutes; the temperature is increased to the third temperature, and the temperature is kept for 20 minutes; the temperature is increased to the fourth temperature, and the temperature is kept for 20 minutes; the temperature is increased to the fifth temperature, and the temperature is kept for 30 minutes.

[0113] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 180°C.

[0114] 3. Add sealing layer After SiO2 and B2O3 are uniformly mixed in a ratio of 1:1: phenolic resin: alcohol = 1:1:0.5, stir for 1 hour to obtain a sealing layer slurry.

[0115] The obtained sealing layer slurry is adhered to the transition layer cured on the carbon-carbon composite material by an impregnation method, so that the thickness of the sealing layer is 0.2 mm, and the carbon-carbon composite material with the transition layer and the sealing layer adhered is transferred to an oven. The curing treatment is carried out according to the temperature increase curve from room temperature to the first temperature, and the temperature is kept for 30 minutes; the temperature is increased to the second temperature, and the temperature is kept for 30 minutes; the temperature is increased to the third temperature, and the temperature is kept for 20 minutes; the temperature is increased to the fourth temperature, and the temperature is kept for 20 minutes; the temperature is increased to the fifth temperature, and the temperature is kept for 30 minutes.

[0116] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 200°C.

[0117] On the one hand, the SiO2 contained in the sealing layer can better compound with the transition layer to prevent the coating from cracking and falling off due to the large difference in thermal expansion coefficients of the two materials; on the other hand, it can increase the sealing temperature, and the added alkaline earth oxide B2O3 can improve the sealing effect.

[0118] 4. Add oxygen barrier Si3N4:SiC:phenolic resin:alcohol=1:1:1:0.5 were mixed and stirred for 1 hour to obtain a slurry for the sealing layer coating.

[0119] The prepared oxygen barrier layer slurry was applied to the carbon / carbon composite material after curing the sealing layer by brushing, so that the thickness of the oxygen barrier layer was 0.3 mm, and then transferred to an oven. The curing treatment was carried out according to the temperature increase curve from room temperature to the first temperature, and kept warm for 30 minutes; to the second temperature, and kept warm for 30 minutes; to the third temperature, and kept warm for 20 minutes; to the fourth temperature, and kept warm for 20 minutes; to the fifth temperature, and kept warm for 30 minutes.

[0120] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 200°C.

[0121] Si3N4 or SiC has unique high temperature oxidation resistance.

[0122] The two elements of silicon nitride have similar electronegativity and are strong covalently bonded compounds. The molecular structure of silicon nitride is complex and diverse. Each silicon atom forms an equivalent Si-N chemical bond with eight nitrogen atoms to form an octahedral structure, which is an atomic crystal and resistant to oxidation at high temperatures. It can also resist thermal shock and will not break even if it is heated to more than 1500°C in the air, cooled rapidly, and then heated rapidly.

[0123] The molecular structure of silicon carbide is formed by carbon and silicon atoms through covalent bonds and ionic bonds, and has two common crystal structures: cubic β-SiC and hexagonal α-SiC. This structure enables silicon carbide to maintain good physical and chemical properties at high temperatures, and has high hardness and wear resistance.

[0124] 5. Add anti-erosion layer After uniformly mixing ZrSiO4:SiC in a ratio of 1:1:phenolic resin:alcohol in a ratio of 1:1:0.5, stir for 1 hour to obtain an anti-erosion layer slurry.

[0125] The prepared anti-erosion layer slurry is adhered to the carbon / carbon composite material of the cured oxygen barrier layer by brushing, so that the thickness of the anti-erosion layer is 0.4 mm, and then transferred to an oven for curing according to a heating curve of heating from room temperature to a first temperature, keeping warm for 30 minutes; heating to a second temperature, keeping warm for 30 minutes; heating to a third temperature, keeping warm for 20 minutes; heating to a fourth temperature, keeping warm for 20 minutes; heating to a fifth temperature, keeping warm for 30 minutes.

[0126] Among them: the first temperature: 80°C; the second temperature: 100°C; the third temperature: 120°C; the fourth temperature: 150°C; the fifth temperature: 200°C.

[0127] The structure of zirconium silicate is a complex silicate structure formed by silicon-oxygen tetrahedrons and zirconium ions through a specific connection method, which makes it have excellent anti-oxidation properties. The coating prepared by mixing ZrSiO4 and silicon carbide in a specific ratio has a very low oxygen permeability and can exist stably at high temperatures above 1500℃ without phase change and reaction, thus having good resistance to oxygen erosion corrosion.

[0128] 6. High temperature furnace sintering The prepared anti-oxidation ceramic coating needs to be sintered at 2300℃ in a high-temperature furnace, and argon is filled for protection throughout the process. During the high-temperature curing process of the transition layer, some SiO2 is infiltrated into the pores of the carbon-carbon material by pressurization. Finally, when sintered at 2200℃ in a high-temperature furnace, SiO2 forms a dense glass structure under high temperature conditions, and the crystal phase is a tetragonal system, which can effectively prevent the chemical reaction between the sealing layer and the base material.

[0129] The different proportions of the main raw materials of Examples 1-5 are shown in the following table, and the blank space indicates that the substance is not present in the examples.

[0130] Comparative Example Comparative Example 1 The steps of Comparative Example 1 are the same as those of Example 1, except that the following ratios are different.

[0131] Comparative Example 2 Firstly, the substrate is ground and polished with 1000 mesh SiC sandpaper. The substrate is a high-purity graphite substrate (purity ≥ 99.99%). Then, the ground and polished substrate is ultrasonically cleaned, dried at 50° C. for 5 h, and then used.

[0132] Weigh the two elemental powders of Zr and Hf in a mass ratio of 0:1 and put them into a beaker, then pour polyvinyl alcohol solution (model: PVA-124, concentration: 0.02g / mL) into the beaker to make the ratio of powder to solution 17g:10mL. Stir with a mechanical stirrer for 30 minutes to obtain a slurry. Apply the slurry evenly on the cleaned substrate by brushing 6 times. Put the substrate coated with the slurry into a blast drying oven, dry and cure at 200°C for 8 hours to form a pre-coated coating for standby use.

[0133] In addition, two single substance powders of Zr and Si were weighed in a mass ratio of 7:3 and put into a ball mill with a ball-to-material ratio of 5:1. Alcohol was used as the ball milling medium. The powders were wet-milled for 10 hours and dried in a blast drying oven. After 5 hours, they were sieved through a 200-mesh sieve to obtain a uniformly mixed evaporation masterbatch.

[0134] The evaporation masterbatch is evenly spread on the bottom of the graphite crucible, and the substrate forming the prefabricated coating is placed 2-5cm above the mixed powder. Finally, the graphite crucible is placed in a high-frequency induction graphitization furnace for heating. When the furnace chamber temperature is 500℃, the furnace is vacuumed until it is below 50Pa; then Ar gas is filled to make the furnace reach one atmosphere. The heating is heated at a rate of 10℃-15℃ / min. When the temperature reaches 2100℃, the furnace chamber is vacuumed again until it is below 50Pa; then Ar gas is filled to make the furnace reach one atmosphere. Continue to heat up to 2200℃, vacuum the furnace chamber for the third time, and fill Ar gas after it is below 50Pa to make the furnace reach one atmosphere. Then keep it at 2200℃ for 2h, and finally cool it with the furnace, with a cooling rate of 5℃ / min.

[0135] A ZrC-HfC / SiC double-layer composite ceramic coating with a thickness of about 300 μm was obtained.

[0136] Test methods for oxidation resistant coatings 1. Thermal shock stability: Heat the sample in a muffle furnace to 1000°C, take it out, and immediately put it into cold water at 10°C. Repeat this process 6 times to observe whether the coating has cracks or falls off.

[0137] 2. Weight loss rate of static oxidation for 2 hours: first weigh the sample, accurate to 0.0002g; place the sample in the center of the muffle furnace that has been raised to the technical conditions, and burn it 20mm away from the bottom of the furnace for 2 hours. During the burning, keep the observation hole of the muffle furnace open to maintain air circulation; take out the sample and place it in a dryer, cool it for 60 minutes, and weigh it, accurate to 0.0002g.

[0138] Where: W-static oxidation 2h weight loss rate; G1-mass of sample before burning, g; G2-mass of sample before ignition, g.

[0139] 3. Coating adhesion test: Test the adhesion of ultra-high temperature anti-oxidation coating according to the national standard GB / T5210-2006.

[0140] 4. Wear value test method after high temperature: After the sample is statically oxidized at 2000℃ for 2h, the wear value test is carried out on the sample. The friction steel wheel is used to produce grinding pits on the surface of the sample under specified conditions, and the thickness before and after grinding is measured to calculate the wear value of the filter plate.

[0141] δ=δ1-δ2 Where: δ - wear value of the sample under specified conditions, μm; δ1 - thickness of the sample before grinding, μm; δ2 - thickness of the sample after grinding, μm.

[0142] The friction steel wheel makes reciprocating motion on the surface of the sample. The linear running speed of the friction steel wheel is set to 0.1m / s. The grinding thickness of the sample is measured after 500 reciprocating times.

[0143] (5) Test method for wear value before high temperature: Same as the above method, except that the sample is before use. For the corresponding embodiment, it is when sintering is completed.

[0144] Test Results The anti-oxidation coatings of the embodiment and the comparative example were subjected to the above test method, and the experimental data are shown in Table 1: Table 1: Anti-oxidation coating experimental data The above embodiments and comparative examples have no cracks, indicating that the samples meet the experimental test conditions, indicating that the oxygen that causes the weight loss rate is not provided by the cracks, which can illustrate the insulation ability of the coating. The coating adhesion of the present application is level 1. Only the components and proportions of the present application can have similar thermal expansion coefficients in the four layers of the preparation after adhesion, drying, and high-temperature sintering, and each function cooperates with each other to achieve good adhesion of the coating. The weight loss rate of the coating of the present application at 1500℃ static oxidation for 2h can be maintained below 0.09%, while the weight loss rate in the comparative example is all above 0.15%. The weight loss rate of the coating of the present application at 2000℃ static oxidation for 2h is 0.11%-0.13%, while this indicator of the comparative example is at least 0.22%. Moreover, through the experimental data difference between the weight loss rate of static oxidation for 2h at 1500℃ and the weight loss rate of static oxidation for 2h at 2000℃, it can be seen that the smaller the difference, the smaller the coating, indicating that the increased temperature has a smaller impact on the oxidation resistance of the coating, indicating that its antioxidant ability is stronger. The wear value of the embodiment of the present application is about 0.02μm before high temperature after sintering, and only about 0.04μm after static oxidation at 2000℃ for 2h. The wear value of the comparative example is twice that of the present application. The coating of comparative example 2 can only withstand 800℃-1000℃, while the present application can withstand 2000℃. Moreover, it can be seen from the wear values ​​of the embodiment itself before and after high temperature that after static oxidation at high temperature of 2000℃ for 2h, its wear value does not increase sharply, indicating that the coating still has good hardness and strength in a long-term high temperature environment. Therefore, the coating of the embodiment of the present application is an anti-oxidation ceramic coating that can withstand ultra-high temperature of 2000℃.

[0145] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing an ultra-high temperature resistant and anti-oxidation ceramic coating, characterized in that: The following steps are involved: (1) Preparation of transition layer Preparing a transition layer slurry: mixing amorphous silicon dioxide, crystalline silicon dioxide, an adhesive, and a solvent in a ratio of (2-4):(1-2):(1-2):(0.5-1), stirring and dispersing the mixture evenly to obtain a transition layer slurry; The transition layer slurry is adhered to the substrate, placed in a curing furnace, and pressurized to obtain A; (2) Preparation of sealing layer Preparation of sealing layer slurry: Mix a mixture of SiO2 and B2O3 in a ratio of (1-2):(2-3), phenolic resin, and alcohol in a ratio of (1-2):(0.5-1):(0.5-1) and stir well to obtain sealing layer slurry; The sealing layer slurry is adhered to A and solidified to obtain B; (3) Preparation of oxygen barrier layer Preparing oxygen barrier layer slurry: mixing Si3N4 or SiC or a mixture of Si3N4 and SiC, phenolic resin, and alcohol in a ratio of (1-2):(0.5-1):(0.5-1) and stirring to obtain oxygen barrier layer slurry; The oxygen barrier layer slurry is adhered to B and cured to obtain C; (4) Preparation of anti-erosion layer Preparation of anti-erosion layer slurry: Mix ZrSiO4 and SiC in a ratio of (0.5-1): (1-2), phenolic resin, and alcohol in a ratio of (1-2): (0.5-1): (0.5-1) and stir evenly to obtain anti-erosion layer slurry; The anti-erosion layer slurry is adhered to C and solidified to obtain D; (5) Sinter D at high temperature in an oxygen-free environment.

2. The method for preparing an ultrahigh temperature resistant and anti-oxidation ceramic coating according to claim 1, characterized in that: The adhesive is an inorganic adhesive, which is silica sol, and the solvent is water. A dispersant is added and stirred evenly to obtain the transition layer slurry.

3. The method for preparing an ultrahigh temperature resistant and anti-oxidation ceramic coating according to claim 1, characterized in that: The adhesive is an organic adhesive, the organic adhesive is a phenolic resin, and the solvent is alcohol.

4. The method for preparing an ultrahigh temperature resistant and anti-oxidation ceramic coating according to claim 1, characterized in that: The transition layer slurry is adhered to the substrate by dipping, painting or electrophoresis, and the sealing layer, oxygen barrier layer and anti-erosion layer slurry are adhered by dipping or painting.

5. The method for preparing an ultrahigh temperature resistant and anti-oxidation ceramic coating according to claim 1, characterized in that: The curing method is: heating from room temperature to the first temperature, keeping it warm for 30 minutes; heating to the second temperature, keeping it warm for 30 minutes; heating to the third temperature, keeping it warm for 20 minutes; heating to the fourth temperature, keeping it warm for 20 minutes; heating to the fifth temperature, keeping it warm for 30 minutes to perform the curing process; Wherein: first temperature: 80°C; second temperature: 100°C; third temperature: 120°C; fourth temperature: 150°C; fifth temperature: 200°C; The pressurized curing method is: pressurizing at room temperature to 1.5-1.8Mp, and the fifth temperature is 180°C.

6. The method for preparing an ultrahigh temperature resistant and anti-oxidation ceramic coating according to claim 1, characterized in that: The substrate is pretreated before preparing the coating. The substrate is a carbon / carbon composite material. The carbon / carbon composite material is polished with SiC sandpaper, ultrasonically cleaned, and dried in an oven.

7. The method for preparing an ultrahigh temperature resistant and anti-oxidation ceramic coating according to claim 1, characterized in that: The amorphous silicon dioxide is 300-400 mesh, and the crystalline silicon dioxide is -200 mesh.

8. The method for preparing an ultrahigh temperature resistant and anti-oxidation ceramic coating according to claim 1, characterized in that: The high temperature sintering temperature in the oxygen-free environment is 2000° C.-2400° C.

9. An ultra-high temperature resistant and anti-oxidation ceramic coating, characterized in that: It includes a transition layer, a sealing layer, an oxygen barrier layer and an anti-corrosion layer, wherein the transition layer includes silicon dioxide, the sealing layer includes SiO2 and B2O3, the oxygen barrier layer includes Si3N4 or SiC or a mixture of Si3N4 and SiC, and the anti-corrosion layer contains ZrSiO4 and SiC.

10. The method for preparing an ultrahigh temperature resistant and anti-oxidation ceramic coating according to claim 9, characterized in that: The thickness of the transition layer coating is 0.2-0.3 mm, the thickness of the sealing layer coating is 0.1-0.2 mm, the thickness of the oxygen barrier layer coating is 0.2-0.3 mm, and the thickness of the anti-erosion layer coating is 0.3-0.4 mm.

Citation Information

Patent Citations

  • Long-term high-temperature oxidation-resistant multi-element composite ceramic coating for carbon / carbon composite material and preparation and application methods thereof

    CN102503581A

  • Yttrium oxide doped calcined mullite-zirconium silicate environmental barrier coating and preparation method thereof

    CN110963824A

  • C / C composite material with surface coating and preparation method thereof

    CN118546017A

  • Carbon-fiber reinforced silicon carbide composite material antioxidation coating layer and its preparation method

    CN1718560A

  • Oxidation resistant c / c composite material and its production

    JP1997241087A